2006
DOI: 10.1016/j.vaccine.2006.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Phase II randomized, placebo-controlled trial of M. vaccae-derived protein (PVAC®) for the treatment of psoriasis

Abstract: The treatment effect against psoriasis of an antigen (delipidated, deglycolipidated form of M. vaccae-PVAC) was investigated. One hundred and sixty-five patients were enrolled in three arms (50 or 15 microg or placebo), each receiving a total of two intradermal injections (days 0 and 21). At week 12, a 75% decrease in psoriasis area and severity index was similar among the studied groups (13, 9 and 18%, p=0.429). The overall incidence of adverse events was significantly higher in the PVAC treated groups when c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Consequently, the authors claimed that PVAC was not an effective immunotherapy for psoriatic arthritis [57]. Likewise, a placebo-controlled study did not show a clearly efficacy of PVAC in the treatment of psoriasis patients, because 75% PASI was similar among the studied groups at week 12 [55].…”
Section: Mycobacterium Vaccaementioning
confidence: 98%
See 1 more Smart Citation
“…Consequently, the authors claimed that PVAC was not an effective immunotherapy for psoriatic arthritis [57]. Likewise, a placebo-controlled study did not show a clearly efficacy of PVAC in the treatment of psoriasis patients, because 75% PASI was similar among the studied groups at week 12 [55].…”
Section: Mycobacterium Vaccaementioning
confidence: 98%
“…The immunotherapy trials began after discovery of the therapeutic effect of M. vaccae injection in psoriasis skin lesions of leprosy patients with concomitant psoriasis [55].…”
Section: Mycobacterium Vaccaementioning
confidence: 99%
“…141 The most rigidly conducted phase 2 study comparison testing of the same M. vaccae formulation ended disappointingly after subjecting patients to a high dose, low dose, and placebo immunotherapy injection 3 wk apart and did not demonstrate a PASI-75 improvement different between groups, with the highest response of 18% seen in the placebo group. 142 The same vaccine did not show a benefit in psoriatic arthritis. 143 Two recent studies, one placebo controlled, have evaluated the use of Mycobacterium w, another non-pathogenic, rapid growing mycobacterial strain in psoriasis and these studies suggested potential benefit with some improvement, but unfortunately the studies lacked rigorous methodology and intergroup comparisons.…”
Section: Potential For Vaccine and Immunotherapy In Psoriasismentioning
confidence: 99%
“…The most rigorous studies have not shown any benefit in psoriasis. 142,143 The most promising development may be immunization against human soluble receptors that are involved in psoriatic diathesis such as TNFα, IL-12, -17, -22, and -23, however, this technology is far from ready for human use. The selection of cytokines to target may be based on the clinical experience with MAbs to these cytokine pathways.…”
Section: Potential For Vaccine and Immunotherapy In Psoriasismentioning
confidence: 99%
“…In two subsequent studies investigating PVAC in psoriasis and PsA patients, it was found to be ineffective. [95,96] Mw (Mycobacterium w) vaccine has been tried in psoriasis patients in small studies. Rath et al [97] conducted a pilot study in which 24 patients received two injections of Mw vaccine at 3 weeks interval.…”
Section: Immunotherapymentioning
confidence: 99%